2021
DOI: 10.22541/au.162567495.57719088/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacokinetically-guided dosing to improve the efficacy of brigatinib in non-small cell lung cancer patients

Abstract: Brigatinib was recently approved for the treatment of anaplastic lymphoma kinase-positive non-small cell lung cancer and is dosed according to a one-dose-fits-all paradigm. We aimed to identify a pharmacokinetically-guided precision dosing strategy to improve treatment response with brigatinib through simulations using a previously published pharmacokinetic-pharmacodynamic model. Dosing strategies explored were the approved 180mg QD, the highest tolerable dose tested in clinical trials: 240mg QD, and two preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies have shown that screening for genetic mutations using ctDNA is highly sensitive and specific, suggesting that ctDNA analysis may significantly improve current tumor detection systems and even aid in early diagnosis. In addition, ctDNA analysis can accurately judge tumor progression, prognosis and assist targeted therapy (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that screening for genetic mutations using ctDNA is highly sensitive and specific, suggesting that ctDNA analysis may significantly improve current tumor detection systems and even aid in early diagnosis. In addition, ctDNA analysis can accurately judge tumor progression, prognosis and assist targeted therapy (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that immunotherapy has become a new trend to replace existing treatment plans. For immunotherapy, different driving genes, different subtypes of driving genes, or co-mutations can all have an impact on clinical efficacy (2). Liquid biopsy, especially circulating tumor DNA (ctDNA) analysis, has been applied in clinical practice as a new non-invasive method for the diagnosis and monitoring of NSCLC.…”
Section: Introductionmentioning
confidence: 99%